Proses Berpikir Mahasiswa dalam Menyelesaikan Masalah Berstandar PISA (Programme for International Student Assesment) - Maryono Maryono (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2020)
One way to measure the development of a country in the main international scale assessment is the PISA (Programme International for Student Assesment). The thinking process of students in solving PISA standard problems can be analyzed using the theory of Assimilation and Accommodation. The approach used in this study is qualitative with the type of case study. The data analyzed in the form of the results of the subject's work when solving problems with PISA standards and the results of interviews with the research subjects. The subject of this study was a prospective student of mathematics at IAIN Tulungagung. The results of the study indicate that the thinking process of students when solving PISA standard problems includes: (a) assimilation: that is, students can directly apply their knowledge to the problems to obtain solutions to problems; and (b) accommodation: i.e. students modify their knowledge to be adapted to existing problems and form new knowledge to suit existing problems.